PERILAKU KONSUMEN TERHADAP PEMBELIAN TELUR AYAM RAS DI PASAR TRADISIONAL KOTA MANADO - Lidya S Kalangi; Lidya Kalangi (Jambura Journal of Animal Science, 2023)
Commercial chicken eggs are one of the most sought-after livestock products by the community due to their easy availability, affordable price, and complete nutritional content to meet the protein needs of animals. This study was conducted to analyze the characteristics of consumers of commercial chicken eggs and examine the factors influencing consumer behavior towards the purchase of commercial chicken eggs in Manado City. The sample determination method used accidental sampling, which involved randomly selecting respondents who were purchasing commercial chicken eggs at the traditional markets of Bersehati and Pinasungkulan in Manado City. A total of 100 respondents were included in the study. The data analysis utilized multiple linear regression analysis. The results indicated that income, the share of expenditure on purchasing commercial chicken eggs, the number of family members, and the education level of housewives simultaneously influenced the dependent variable, which was the quantity of consumed commercial chicken eggs. The R2 value of 0.545 indicates that changes in the independent variables can explain 54.5% of the changes in the dependent variable, while the remaining 45.5% is attributed to other factors beyond the model equation. The characteristics of consumers of commercial chicken eggs in the traditional markets of Bersehati and Pinasungkulan in Manado City include age, education level, occupation, and income.